THE EFFECT OF EXPERIENCE QUALITY ON THE INTENTION TO VISIT AGAIN BY TOURIST EXPERIENCE AND DESTINATION ATTRACTIVENESS ON THE DECISION TO VISIT TOURIST DESTINATIONS: CUSTOMER SATISFACTION AS MEDIATION - Danang Apriliyanto; Etty Widawati (Jurnal Scientia, 2023)
This study aims to analyze whether the quality of experience has a significant effect either directly or indirectly on the intention to visit again at Pasar Splendid Malang Shopping Object mediated by satisfaction. This type of research is explanatory research that explains causal relationships between variables through hypothesis testing. The sample of this study was one of 100 respondents obtained by purposive sampling method. The data analysis method in this study using path analysis with SmartPLS 3.0 software was used to test the relationship of mediation variables in the hypothesis. The results showed that the quality of experience had a significant influence both directly and indirectly on the intention to revisit with satisfaction as a mediating variable in visitors to the Splendid Market Shopping Object Malang City.